Pretreatment of phosphating wastewater with different advanced oxidation processes - ZHANG Chenfei; HE Can; ZHANG Zhongguo; WANG Jianbing; ZHANG Jian; WANG Mengyu; SUN Hongfang; HU Zhifeng; GONG Chenhao; HAN Junxing; SHAN Yue (Gongye shui chuli)
The effects of three oxidation processes, ozone (O3) oxidation, O3/potassium peroxymonosulfate (PMS) oxidation, and O3/hydrogen peroxide (H2O2) oxidation, on the treatment of phosphating wastewater were compared. Additionally, the quality of effluent was analyzed through measurements of COD, UV254, and three-dimensional fluorescence spectra, highlighting the influence of various advanced oxidation processes on the wastewater effluent quality and the removal pathways. The results showed that increasing the ozone dosage and adding appropriate amounts of PMS and H2O2 could enhance the removal of organic contaminants from phosphating wastewater. With initial COD of (130±20) mg/L, reaction time of 120 minutes, and ozone dosage of 7.65 mg/min, the COD removal rate was only 37% by the ozonation process, the COD removal rate reached 45.65% by the O3/PMS oxidation process with PMS mass concentration of 2 g/L, the COD removal rate reached 58.3% by the O3/H2O2 oxidation process with 0.5 g/L dosage of H2O2 (30% concentration). Among the three methods, the O3/H2O2 process demonstrated the highest efficacy in removing COD from phosphating wastewater, as the synergistic production of more highly oxidative free radicals by O3 and H2O2 enhancd the oxidation capacity of the system. All three processes effectively degraded aromatic compounds and fluorescent substances in wastewater, while the individual O3 oxidation and the O3/PMS process mainly degraded substances resembling proteins into fulvic and humic-like materials, and the O3/H2O2 oxidation process could further degrade these fulvic and humic-like substances.